Short-course blinatumomab for refractory/relapse precursor B acute lymphoblastic leukemia in children - Xie, Jiao; Liu, Suxiang; Zhou, Ming; Wang, Yi; He, Hailong; Xiao, Peifang; Hu, Shaoyan; Lu, Jun (Frontiers in Pediatrics, 2023)
Objective: To evaluate the clinical efficacy and safety of a short course of blinatumomab in children with refractory or relapsed precursor B-cell acute lymphoblastic leukemia (R/R-BCP-ALL).The clinical data of 33 R/R BCP-ALL children aged 0-18 years who underwent a short course of blinatumomab (14 days) between August 2021 and November 2022 were retrospectively collected and analyzed.Results: Among 33 patients with BCP-ALL, 26 achieved complete remission (CR), with a total remission rate of 78.8% (26/33). The duration of remission was approximately 14 days. Of the 7 children without CR, 5 were still in remission at 28 days. In 11 patients with refractory disease and 22 with recurrence, the remission rates were 90.9% (10/11) and 72.7% (16/22), respectively. The overall survival (OS) rates of the 26 patients with CR and seven patients without CR were 96.1% and 57.1 % (p = 0.002), respectively, and the disease-free survival (DFS) rates were 96.1% and 42.9% (p<0.001), respectively. Among the 26 patients with CR, 15 underwent bridging hematopoietic stem cell transplantation (HSCT) and 11 did not receive HSCT; with OS rates of 93.3% and 100% (p=0.40) and DFS rates of 93.3% and 100% (p = 0.400), respectively. The OS for all patients was 87.9% (29/33) and the DFS was 84.8% (28/33). There were 18 cases (54.5%) of cytokine release syndrome (CRS), 2 cases (6.1%) of severe CRS (all grade 3), 1 case (3.0%) of immune effector cell-associated neurotoxicity syndrome (ICANS), 0 cases (0%) of ICANS ≥ grade 3, and no deaths caused by treatment.Conclusions: Short-term follow-up revealed a high R/R BCP-ALL remission rate in children treated with a short course of blinatumomab. The toxicity was low and controllable. No significant short-term survival benefits were observed after bridging HSCT with blinatumomab. In developing countries, a short course of blinatumomab can achieve satisfactory outcomes, while reducing household costs and saving medical resources.